Relationship between parenting style parental competence on emotional intelligence of college students in urban area of Anambra State, Nigeria - Joseph, Okoye Chukwuebuka (2021)
Emotional intelligence (EI) refers to the ability to identify and manage individuals' emotions as well as the emotions of others. Since parenting styles and competence predict many aspects of the college students’ wellbeing, it makes more sense to believe that they can also have significant impacts on the EI of college students. Despite many studies having been conducted on the parenting styles, no attention has been paid to address the relationships between parenting style and parental competence on emotional intelligence of college students in the urban area of Anambra State, Nigeria. The current study concerns with college students as there is a need to describe the relationship between parenting style and parental competence on EI because this population category may soon start parenting their children who are in colleges. This study involved 320 college students in the urban area of Anambra State, Nigeria. A self-administered questionnaire was used in the data collection. Research instruments used were Parental Authority Questionnaire-PAQ by Baumrind (1971), Perceptions of Parents Scale (POPS) by Grolnick et al (1997) and The Schutte Self Report Emotional Intelligence Test (SSEIT) by Schutte’s (1999). The findings demonstrated that permissive parenting of the mother was significantly correlated (r = .185, p < .01) with the students’ emotional intelligence. Authoritative parenting of the mother was also significantly correlated (r = .242, p < .01) with students’ emotional intelligence. Parental competence of the mother was also significantly correlated (r = .200, p < .01) with the students’ emotional intelligence. The regression analysis found that the mothers’ authoritativeness positively and significantly predicted college students’ emotional intelligence (β = .188, t = 2.894, p < .05). The study concluded mothers’ permissive and authoritative parenting styles and mothers’ parental competence positively and significantly correlated with emotional intelligence of College Students in the Anambra State, Nigeria. Therefore, to ensure higher emotional intelligence students when they reach the college level, parents should adopt either permissive or authoritative parenting styles.